Dairy industry wastewater as a sustainable alternative to increase the productivity of corn in Peru - Del Carpio Salas, Miguel Angel (2021)
Corn (Zea Mays) is the most cultivated cereal in the world and this is a staple food for human beings that is why in recent years they are looking for alternatives to improve their production. On the other hand, whey is a residual effluent from the dairy industry generally eliminated in sewage, however, due to its high organic load it can be used to produce different biofertilizers. The objective of this study was to evaluate the effect on the production of the corn crop when applying a biofertilizer obtained by anaerobic fermentation of whey and bovine manure. The study was conducted between October 2018 and February 2019, in the experimental area of ​​the Calaspam association, located in Majes, Arequipa-Peru. A complete randomized block experimental design was used in a 2×4 factorial scheme composed by three biofertilizer treatments (6.9 and 12 LBF/water) and a control treatment with three replicates applied with an average flow rate of 1.5 Lha-1. Morphological, post-harvest and economic indicators were determined, as well as the chlorophyll content. Results indicate that biofertilizer treatments improved the indicators studied. The third treatment shows higher values in all the indicators compared to the other treatments, being the values of yield (79,29±7,33 103 kgha-1) and marginal return rate (85,73%) the most outstanding. It is concluded that the biofertilizer obtained from bovine manure and whey has a positive effect on corn production and its application is economically viable.